Pengaruh Pengawasan dan Disiplin Kerja Terhadap Kinerja Karyawan pada Perusahaan PT. Aerofood ACS Medan - Helena Pitri Susanty Situmorang; Martua Sitorus (Junal Ilmu Manajemen, 2018)
This study aims to determine the effect of work supervision and discipline on employee performance in the company PT. Aerofood ACS Medan. The object of this research is PT. Aerofood ACS Medan. The sampling technique uses the Slovin formula with population of PT. Aerofood ACS Medan. Data collection was obtained through distributing questionnaires to 98respondents. The collected data were analyzed using multiple linear regression analysis with thesignificance level used was 5%. The results of this study indicate that the independent variables, namely supervision (X1)and work discipline (X2), have a positive and significant effect on employee performanceat PT. Aerofood ACS Medan. The test results are carried out with a partial test (t test) andproduce the conclusion that the null hypothesis is rejected. Thus it is known that employee performance is influenced by supervision and work dicipline.